Pengaruh Fluida Pendingin Terhadap Kapasitas Radiator Dan Efektifitas Absorbsi Panas Pada Mesin Toyota Avanza 1.3 G M/T - Kusnanto, Hadi; Batutah, Moh Arif (Motor Bakar : Jurnal Teknik Mesin, 2025)
The cooling system is an important part in an engine work cycle. The main purpose of the cooling system is to maintain the engine's working temperature to remain optimal and prevent overheating in the engine. Therefore, the researcher examines the variation of the cooling fluid on the radiator capacity and effectiveness of heat absorption and analyzes the radiator capacity based on the engine rpm and the effect of time on the capacity and effectiveness of heat absorption. This research is using experimental method. The testing process is carried out in stages and records the test results. The results of calculations and tests for the heat transfer rate (radiator capacity) are the highest on mineral water fluid, namely 810117 watts and the lowest on Super long life Coolant fluid, namely 170319.6 watts. While the test results for the effectiveness of radiator heat absorption which has a stable heat absorption effectiveness from the variation of the applied fluid is using Super long life Coolant fluid